Radix Aucklandiae (dried root of Saussurea costus)-induced acute generalized exanthematous pustulosis confirmed by patch testing - Po-Han Ho; Yung-Tsu Cho; Chia-Yu Chu (Wolters Kluwer Medknow Publications, 2019)
A 40-year-old female presented with rapid-onset generalized erythematous eruption with pustules agminated over the flexural areas and the flanks for 2 days. In skin histopathology, extensive subcorneal pustules, spongiosis and neutrophilic exocytosis, papillary dermal edema, and perivascular and interstitial mixed-cell infiltrates were observed. No psoriasis history but irregular intake of numerous kinds of Chinese herbal medications and the last-modified regimen including Radix Aucklandiae 14 days before the onset of pustular eruption were unveiled. Patch test showed positive result with only Radix Aucklandiae. Thus, acute generalized exanthematous pustulosis induced by Radix Aucklandiae was diagnosed.